Endothelial to mesenchymal transition (EndMT) and vascular remodeling in pulmonary hypertension and idiopathic pulmonary fibrosis. (2nd October 2020) - Gaikwad, Archana Vijay; Eapen, Mathew Suji; McAlinden, Kielan D.; Chia, Collin; Larby, Josie; Myers, Stephen; Dey, Surajit; Haug, Greg; Markos, James; Glanville, Allan R.; Sohal, Sukhwinder Singh
ABSTRACT: Introduction: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, and irreversible fibrotic disease associated with respiratory failure. The disease remains idiopathic, but repeated alveolar epithelium injury, disruption of alveolar-capillary integrity, abnormal vascular repair, and pulmonary vascular remodeling are considered possible pathogenic mechanisms. Also, the development of comorbidities such as pulmonary hypertension (PH) could further impact disease outcome, quality of life and survival rates in IPF. Areas covered: The current review provides a comprehensive literature survey of the mechanisms involved in the development and manifestations of IPF and their links to PH pathology. This review also provides the current understanding of molecular mechanisms that link the two pathologies and will specifically decipher the role of endothelial to mesenchymal transition (EndMT) along with the possible triggers of EndMT. The possibility of targeting EndMT as a therapeutic option in IPF is discussed. Expert opinion: With a steady increase in prevalence and mortality, IPF is no longer considered a rare disease. Thus, it is of utmost importance and urgency that the underlying profibrotic pathways and mechanisms are fully understood, to enable the development of novel therapeutic strategies.